Synthesis, Anti-Tumor Activity and Apoptosis-Inducing Effect of Novel Dimeric Keggin-Type Phosphotungstate - Xue, Yingxue; Yin, Yifei; Li, He; Chi, Mingyu; Guo, Jiaxin; Cui, Guihua; Li, Wenliang (Frontiers in Pharmacology, 2021)
A dimeric Keggin-type phosphotungstate (ODA)10[(PW11FeO39)2O]·9H2O (abbreviated as ODA10[(PW11Fe)2], ODA= octadecyltrimethylammonium bromide) was synthesized and investigated comprehensively its antitumor activity on MCF-7 and A549 cells. The dimeric structure and amorphous morphology were characterized by FT-IR, UV-vis-DRS, SEM and XRD. The in vitro MTT assay of ODA10[(PW11Fe)2] showed anticancer activity on MCF-7 and A549 cells in a dose- and time-dependent manner, and the IC50 values for MCF-7 and A549 cells at 48 h were 5.83 μg/mL and 3.23 μg/mL, respectively. The images of the ODA10[(PW11Fe)2]-treated cells observed by inverted biological microscope exhibited the characteristic morphology of apoptosis. Flow cytometric analysis showed cell apoptosis and cycle arrested at S phase induced by ODA10[(PW11Fe)2]. The above results illuminated the main mechanism of the antitumor action of ODA10[(PW11Fe)2] on MCF-7 and A549 cells, indicating that this dimeric phosphotungstate is a promising anticancer drug.